Lise ekoloji konularının disiplinler arası öğrenci merkezli öğretiminin başarıdaki rolü - Çimen, Selime (My University, 2002)
Today, the importance of environmental education to maintain a livible environment and sustainable development is understood by all countries. Environmental education curriculum, teaching methods and subject knowledge of teachers are the three important factors that affect ecology education as a part of environmental education. Student centered ecology education with an interdisciplinary approach leads to more conceptual learning rather than teacher centered ecology education in students. The aim of this research is to show how an interdisciplinary student centered ecology teaching increases student success. In addition to that, a teacher survey is carried out to understand if student centered ecology education is applicable in state schools and private schools. This research was carried out in a private high school in İstanbul city limit with an experimental group of 20 students that have learned ecology by student-centered teaching and a control group of 20 students that have learned ecology by teacher-centered teaching strategies. Ecology knowledge of the experimental group and the control group students were measured by a pre-ecology test, a written midterm exam and a post-ecology test. The environmental attitude of the experimental group students and the control group students were also measured by a pre-test and a post-test. The results of ecology pre, midterm and post tests and environmental attitude tests were analysed by statistical methods. A questionnaire for 20 questions was also given to 95 biology teachers to determine if student-centered ecology education is applicable in their teaching stuations. The results of the students' knowledge tests show that interdisiplinary student-centered ecology teaching leads to more conceptual learning than teacher- centered ecology teaching. It is also understood that, short term student centered ecology education does not change the environmental attitude of students. The results of the teacher survey show that interdisciplinary student centered ecology education can not be carried out under the existing conditions of state schools. The results also show that teachers need in service training to improve their subject knowledge and to learn active learning strategies.
Keywords: Eğitim